2021
DOI: 10.1021/acs.jpcb.0c08969
|View full text |Cite
|
Sign up to set email alerts
|

Ranking the Efficiency of Gas Hydrate Anti-agglomerants through Molecular Dynamic Simulations

Abstract: Using both computational and experimental methods, the capacity of four different surfactant molecules to inhibit the agglomeration of sII hydrate particles was assessed. The computational simulations were carried out using both steered and non-steered molecular dynamics (MD), simulating the coalescence process of a hydrate slab and a water droplet, both covered with surfactant molecules. The surfactants were ranked according to free energy calculations (steered MD) and the number of agglomeration events (non-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…This mechanism is very similar to the behavior of AAs in preventing the aggregation of hydrate particles. That is, an interfacial film was generated at a sufficiently high surface density of AAs, resulting in a barrier that impeded approaching water droplets and methane molecules to the hydrate particles. , Experimental results further revealed that a thicker barrier was measured with a longer AAs alkyl chain by evaluating the cohesive forces between gas hydrate particles . With respect to the similar alkyl group of AAs, the AAI corrosion inhibitor actually acted as an anti -agglomerant to prevent gas hydrates from reaching the pipeline surface.…”
Section: Resultsmentioning
confidence: 98%
“…This mechanism is very similar to the behavior of AAs in preventing the aggregation of hydrate particles. That is, an interfacial film was generated at a sufficiently high surface density of AAs, resulting in a barrier that impeded approaching water droplets and methane molecules to the hydrate particles. , Experimental results further revealed that a thicker barrier was measured with a longer AAs alkyl chain by evaluating the cohesive forces between gas hydrate particles . With respect to the similar alkyl group of AAs, the AAI corrosion inhibitor actually acted as an anti -agglomerant to prevent gas hydrates from reaching the pipeline surface.…”
Section: Resultsmentioning
confidence: 98%
“…Advanced surface science is a prerequisite for the development of targeted LDHIs. ,, As surface-active reagents, LDHIs adsorb on the surface of ensuing hydrate nuclei and retard their growth and/or aggregation. , This necessitates an insightful understanding of the interaction between LDHI molecules and the hydrate surface. , The attractive force between LDHI molecules and the hydrate surface (i.e., the driving force of LDHIs adsorption) acts within a subnanometer range, meaning that the adsorption process is dictated only by a few outmost water layers of the hydrate surface. Carver et al indicated that this driving force arises from the hydrogen bonding between hydrophilic sites of LDHI molecules and water molecules of the hydrate surface. , This mechanism applies to hydrate surfaces contacting a gas or hydrophobic environment.…”
Section: Applications In Sustainable Technologiesmentioning
confidence: 99%
“…In addition, computer simulations offer a useful complementary tool for studying the structure and dynamics of the premelting layer as well as the behavior of additive molecules at hydrate surfaces. , , Future simulations would benefit from the latest advances in the computational techniques such as machine learning that will further expand the capability of simulations and enable the possibility to deal with complex systems such as large samples, long simulation time and complex interactions with reasonable computational costs. New water models and force fields will be required to capture the complex behavior of water molecules and their hydrogen bonds to generate reliable and more realistic simulation outputs (discussed in the next section: Grand Challenges).…”
Section: Prospects and Challengesmentioning
confidence: 99%